3 USM SCIENTISTS RECEIVE MALAYSIA'S RISING STAR AWARD AND 6 JOURNALS ACCORDED 'CREAM' STATUS BY MALAYSIAN HIGHER EDUCATION MINISTRY - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PUTRAJAYA, 1 November 2016 Three scientists from Universiti Sains Malaysia (USM) received the Malaysia's Rising Star Award while 6 journals from Penerbit USM (USM Press) were awarded the CREAM status by the Malaysian Ministry of Higher Education in a ceremony presented by the Minister of Higher Education, Dato' Seri Idris Jusoh at the Marriott Hotel in Putrajaya today.